Book review: Stuart, David. Web metrics for library and information professionals - Elena Maceviciute (Information Research: An International Electronic Journal)
Stuart, David. Web metrics for library and information professionals. 2nd ed. London: Facet Publishing, 2023. xvi, 206 p. ISBN 978-1-78330-566-7